Bioatividade de extratos de três espécies de Solanum sobre Cryptotermes brevis e Spodoptera frugiperda - Cainelli, Vânia Rech (My University, 2014)
Two of the major pests that damage property and cultural goods as well as threaten crop productivity and yields are Cryptotermes brevis (dry-wood-termite) and Spodoptera frugiperda (fall-armyworm-cartridge).Looking for new and natural sources to control them, we investigated the antiinsect activity of three american Solanum species on these two pests. The genus Solanum is one of the most diverse in South America and many of its representative s biosynthesed different chemical compounds with proven bioactivity against insect pests. In the present study, the antifeedant and repellent effects on C. brevis of dichloromethane, dichloromethane/acetone (enriched fraction sugar esters) and aqueous/alcoholic extract obtained from Solanum bonariense, Solanum bistellatum and Solanum sisymbrifolium were evaluated. The extracts from the three plant species showed antifeedant and repellent effect against C. brevis, especially dichloromethane and dichloromethane / acetone extracts from S. sisymbrifolium and S. bistellaltum. The results obtained from these extracts of the three evaluated species indicate the presence of bioactive compounds with potential bioactivity against C. brevis. We also evaluated the effect of dichloromethane and dichloromethane/acetone extracts from S. bonariense and S. sisymbrifolium and the two major compounds I and II (sugar esters) isolated from the dichloromethane / acetone extract of S. sisymbrifolium on the development of S. frugiperda. In the tests performed with S. frugiperda it was observed that the addition of S. sisymbrifolium extracts affected the number of larval instars, and the dichloromethane extract had less effect on the larval stage and a pronounced effect on the pupae. The S. sisymbrifolium dichloromethane/acetone extract affected more than the larval pupae and induced a decrease in survival with a dose dependent response. The dichloromethane S. bonariense extract did not affect the number of larval instars but minimally influenced the S. frugiperda larval and pupal behaviour, however the dichloromethane / acetone extract affects the number of larval instars, and the larval, pupal and total development were less affected. The most effective extract evaluated against S. frugiperda was the S. sisymbrifolium dichloromethane/acetone extract representing an enriched fraction of sugar esters. Two major components were isolated: I and II, they were also evaluated on S. frugiperda and proved to be highly toxic to fall-armyworm-cartridge larvae from with 0.46% overall survival at concentration 2.5 mg / mL for compound I, and 11.11% overall survival at concentration 1 mg / mL for compound II. These isolated compounds also affected the metamorphosis of the caterpillar to the pupa stage. Structural elucidation of the isolated compounds from the species S. sisymbrifolium and S. bistellatum was performed using NMR and Gas Chromatography. In both species the presence of esters of sugars was determined; a disaccharide esterified with long chain fatty acid, mainly palmitic and hidroxipalmitic acid. The discovery of bioactive substances represents an alternative to the use of natural insecticides in pests control that gave higher safety and environmental sustainability.
O gênero Solanum é um dos mais diversos na América do Sul e seus representantes apresentam compostos químicos com bioatividade contra insetos-praga. Entre as principais pragas que provocam danos econômicos tanto a bens culturais e imóveis como na agricultura encontram-se Cryptotermes brevis (cupim-de-madeira-seca) e Spodoptera frugiperda (lagartado- cartucho). No presente estudo avaliou-se os efeitos antialimentar e repelente dos extratos diclorometânico, extrato diclorometano/acetona (fração enriquecida em ésteres de açúcares) e extrato aquo-alcooólico obtidos de Solanum bonariense, Solanum bistellatum e Solanum sisymbrifolium sobre C. brevis. Avaliou-se também o efeito dos extratos diclorometânico e diclorometano/acetona de S. bonariense e S. sisymbrifolium e dois compostos majoritários I e II (ésteres de açúcares) isolados do extrato diclorometano/acetona de S. sisymbrifolium sobre o desenvolvimento de S. frugiperda,. Os extratos obtidos das três espécies vegetais demonstraram ação antialimentar e repelente ao cupim C. brevis, especialmente os extratos diclorometânico e diclorometano/acetona de S. sisymbrifolium e de S. bistellaltum. Os resultados obtidos com os extratos destas duas espécies indicam a existência de compostos bioativos com potencial para o controle de C. brevis. Nos ensaios com S. frugiperda observase que a adição dos extratos de S. sisymbrifolium afetaram o número de ínstares larvais, sendo que o extrato diclorometânico teve menor efeito sobre a fase larval e acentuado efeito sobre as pupas. O extrato diclorometano/acetona de S. sisymbrifolium afetou mais a sobrevivência larval do que a pupal, e induziu uma diminuição na sobrevivência com uma resposta dose dependente. O extrato diclorometânico de S. bonariense não afetou o número de ínstares larvais e afetou minimamente a sobrevivência larval, pupal e total de S. frugiperda, e o extrato diclorometano/acetona afetou o número de ínstares larvais, sendo a sobrevivência larval, pupal e total pouco afetadas. O extrato mais efetivo foi diclorometano/acetona de S. sisymbrifolium que representa uma fração enriquecida de ésteres de açúcares, do qual isolou-se os compostos majoritários I e II, que demonstraram ser altamente tóxicos na fase larval de S. frugiperda com 0,46% de sobrevivência total na concentração 2,5 mg/mL para o composto I, e 11,11% de sobrevivência total na concentração 1 mg/mL para o composto II. Estes compostos isolados também afetaram a metamorfose da lagarta para o estágio de pupa. A elucidação estrutural dos compostos isolados das espécies S. sisymbrifolium e S. bistellatum foi realizada por RMN e Cromatografia Gasosa podendo determinar em ambas espécies a presença de ésteres de açúcares: dissacarídeos esterificados com ácidos graxos de cadeia larga, principalmente acido palmítico e hidroxipalmitico. A descoberta de substâncias bioativas representa uma alternativa ao uso de inseticidas naturais para controle de pragas, que apresentem maior segurança e sustentabilidade ao meio ambiente.
Keywords: Ciências Agrárias; Solanum; Inseticidas; Biotecnologia; Pragas - Controle; Solanum; Insecticides; Biotechnology; Pests control